Mirada de viajeros e historiografía: la campaña de Buenos Aires al concluir el s. XVIII (Estudios) - Dupuy, Andrea; Rosas Principi, Andrea; Ciliberto, María Valeria (Quito: Universidad Andina Simón Bolívar, Corporación Editora Nacional, Taller de Estudios Históricos, 2008)
El artículo revisa los relatos de Francisco de Amigorena y de Alexander Gillespie, un funcionario y un militar, escritos a fines del siglo XVIII e inicios del XIX, que han sido la base de la historiografía tradicional argentina sobre el mundo rural de Buenos Aires. Desde la perspectiva de la nueva historiografía económica argentina y de la historia del paisaje, replantea la imagen de la conformación de las clases dominantes rurales de la época y el papel económico del interior de la pampa de la provincia de Buenos Aires. Específicamente, el artículo cuestiona la idea de un espacio desierto, tal como la pintó la historiografía romántica, y propone el perfil de un hinterland heterogéneo, dedicado a distintas actividades.

This article reviews the accounts of Francisco de Amigorena and Alexander Gillespie, a functionary and soldier, written at the end of the 18th Century and beginning of the 19th Century. These accounts formed the basis of the traditional Argentinian historiography of the rural areas of Buenos Aires. From the perspective of the new economic historiography in Argentina and of rural history, the article rethinks the image of the structure of the dominant rural classes of the age and the economic role of the interior of the pampa of the province of Buenos Aires. Specifically, the article questions the idea of the countryside as a deserted space such as it had been depicted in the romantic historiography, and the article proposes the outline of a heterogeneous hinterland dedicated to several activities.
The traveler's Gaze and Historiography: the Buenos Aires Countryside an the end of the 18th Century and beginning of teh 19th Century
Keywords: HISTORIOGRAFÍA; HISTORIA; VIAJES; PAISAJE; CAMPAÑA DE BUENOS AIRES; HISTORIOGRAPHY; HISTORY; VOYAGES AND TRAVELS; LANDSCAPE; CAMPAIGN OF BUENOS AIRES